Scientific analysis of a preserved head of hair at Romsey Abbey, UK. (June 2017) - Cameron, Jamie; Devièse, Thibaut; Green, Francis
Abstract: This paper presents the results of a scientific investigation on a preserved head of hair, discovered in 1839 inside a lead coffin beneath the Norman Abbey of Romsey (Hampshire, UK). Accelerator mass spectrometry (AMS) radiocarbon dating, modelled to account for dietary marine protein intake indicated by stable isotope analysis (δ 13 C and δ 15 N), suggests that this individual died between 895–1123 calAD (95.4% probability). A wooden 'pillow' found supporting the hair produced a date of 895–1016 calAD (95.4% probability). These results suggest that this burial dates from the end of the ninth century to the early twelfth century, placing it in the late Saxon or immediately post-Conquest era. Analysis by Gas Chromatography/Mass Spectrometry (GC/MS) of residue adhering to the hair surface indicates the presence of Pinacea resin, deriving either from funerary ritual or hair care during life. Highlights: A preserved head of hair discovered in 1839 has been scientifically analysed. The hair has been radiocarbon dated to 895–1123 calAD (95.4% probability). The supporting wooden 'pillow' dates to 895–1016 calAD (95.4% probability). Isotopic analysis indicates a significant proportion of dietary marine protein. Molecular analysis has revealed the presence of Pinacea resin applied to the hair.